2019
DOI: 10.3390/sports8010002
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Collapsing Half Marathon Runners—Emerging Risk Factors: Results from Gothenburg Half Marathon

Abstract: Among several serious medical conditions, arrhythmia and heat stroke are two important causes of death during endurance races. Clinically, collapsing might be the first sign of these serious conditions and may mimic the more common and benign exercise-associated collapse. Several risk factors have been reported in the literature. We aimed to conduct a qualitative study to find a perceived risk profile among runners who collapsed and who were transported by ambulances to the nearest hospital during Gothenburg’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
1
10
1
1
Order By: Relevance
“…Based on our results, about 90% of cardiac arrests in marathons are caused by myocardial infarctions, arrhythmias and cardiogenic cardiac arrests due to acute cardiac failure. Cardiogenic cardiac arrests constitute the majority of cardiac arrests that occur during marathons 14–19. More than 80% of the AED-applied cases were shockable; hence, we assume that the majority of the initial ECG rhythms of cardiac arrests in marathons was due to VF 17.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, about 90% of cardiac arrests in marathons are caused by myocardial infarctions, arrhythmias and cardiogenic cardiac arrests due to acute cardiac failure. Cardiogenic cardiac arrests constitute the majority of cardiac arrests that occur during marathons 14–19. More than 80% of the AED-applied cases were shockable; hence, we assume that the majority of the initial ECG rhythms of cardiac arrests in marathons was due to VF 17.…”
Section: Discussionmentioning
confidence: 99%
“…For older respondents, health orientation was especially important. However, health control and educational information before races might be a necessary step to avoid life-threatening complications because studies have shown that runners are often unable to stop despite disturbing symptoms and the desire to finish the run may expose them to life-threatening effects (Khorram-Manesh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found that several subjects in the morning had a dark yellow urine color; after being traced, it turned out that the habit of consuming tea and vitamins affects the work of the kidneys, resulting in yellow urine (into the urine color scale 4-6) which indicates that there is an infection. Dehydration is usually characterized by loss of focus (Perrier, 2017;Pritchett et al, 2020), muscle cramp (Maughan & Shirreffs, 2019), heat stroke (Kenney et al, 2015;Porcari et al, 2015), and the worst is collapsing (Khorram-Manesh et al, 2020;Lüning et al, 2019;Thorsson et al, 2021).…”
Section: Resultsmentioning
confidence: 99%